Endodontic Treatment Of Unusually Long Discolored Maxillarycentral Incisor: A Case Report (2013)
Background: Success in root canal treatment is achieved after thorough bio mechanical preparation followed by complete obturation of the canal system together with prompt and adequate restoration. Therefore, the endodontic therapy requires specific and complete knowledge of the internal and external anatomy, and its variation in presentation. Such treatment may be performed in root canal systems that do not comply with normal anatomic features described in standard textbooks. This article presents a case of endodontic treatment in an unusually long discolored maxillary central incisor. Case Presentation: A 31 year-old male patient was referred to conservation clinic for endodontic treatment of discolored left maxillary central incisor with associated history of recurrent swelling. Root canal therapy was performed and patient was found to have an unusually long working length of 29mm. This was then followed by enucleation of apical cyst without apical resection. Conclusion: Though the patient presents a maxillary central incisor with canal length in the upper limit of some reported cases, it is unusual in our environment.